AIDS with obesity, hypothyroidism and elevated serum creatinine: A case report - Zhang, Chenxi; Qian, Chuyue; Wang, Wanning; Chen, Zhi; Lin, Yangyang; Sun, Mindan (Frontiers in Medicine, 2023)
Hypothyroidism is a prevalent endocrine illness with a variety of clinical symptoms, but among which elevated serum creatinine is uncommon. Hypothyroidism is also common in acquired immunodeficiency syndrome (AIDS) patients, especially those receiving highly active antiretroviral treatment (HAART). Here we present a case of a young AIDS patient with hypothyroidism, increased serum creatinine, and obesity. Despite the lack of a kidney biopsy, following levothyroxine (LT4) therapy, his serum creatinine recovered to normal levels, and weight loss, edema, weakness, rough skin and other clinical symptoms obtained notable improvement. This highlights the need of clinicians paying attention to whether thyroid function is aberrant in human immunodeficiency virus (HIV) patients with increased creatinine, edema and significant weight gain since prompt thyroid hormone therapy can restore the alterations in renal function and avoid invasive renal biopsy.